Acetylenic bond-driven efficient hydrogen production of a graphdiyne based catalyst. (23rd February 2021) - Bai, Ling; Zheng, Zhiqiang; Wang, Zhongqiang; He, Feng; Xue, Yurui; Wang, Ning
Abstract : 3D acetylenic bonds distributing makes tetraphenyl methane substitute graphdiyne (TPM-GDY) show more active sites and high hydrogen evolution reaction performance. Abstract : The presence of acetylenic bonds in graphdiyne (GDY) endow this type of carbon allotrope with high intrinsic catalytic activity, which is significantly superior to traditional carbon materials. Here, a synthetic strategy has been developed to study the influence of active acetylenic bond ratio and spatial distribution on the hydrogen evolution reaction (HER) catalytic performance. Two kinds of GDY, namely tetraphenylmethane-graphdiyne (TPM-GDY) and triphenylamine-graphdiyne (TPN-GDY), have been rationally synthesized via a bottom-to-up synthetic strategy. From the structural view, both TPM-GDY and TPN-GDY possess the 1, 4-diphenylbuta-1, 3-diyne skeleton composed of electrocatalytic active sp carbon. TPM-GDY possesses more active sp carbon exposed to the surface than TPN-GDY, which makes the TPM-GDY electrode exhibit better HER performance. Besides, some other properties of GDY-based carbon materials such as morphology, surface area, and pore distribution can also be efficiently adjusted. The above-mentioned results indicate that the distribution of active sites in the carbon framework plays a critical role in improving the catalytic performances, which offers a new strategy for creating highly active and stable electrocatalysts.